Solution and key technology of integrating vFW in cloud platform - Zhilan HUANG; Yongbing FAN; Ning FAN; Nan CHEN; Linze WU; Baohong LIN (Dianxin kexue)
FWaaS is one of the key cloud network services,which requires ability of auto provisioning and flexibility of on-demand adjustment.It is suitable for cloud platforms to provide FWaaS based on virtual firewalls (vFW) appliance.vFW has its own particularity comparing to other cloud components.It is not only a network service but also a network element,which should be orchestrated by business systems and should be automatically configured by network systems.In the environment of cloud resource pool,vFW faces the integration problem with other cloud components like SDN and cloud management platform.The main method of integrating vFW in cloud resource pool was studied,the existing integration problems were analyzed,and an integration method based on extensible model driven framework was proposed.